Identifikasi ekstrak bunga telang (Clitoria Terenatea L.) sebagai bahan alami makanan - Widyawati, Aprilia (Maliki Interdisciplinary Journal, 2024)
Butterfly pea flower or Clitoria ternatea Linn is a legume plant that is easy to plant and thrives in the sun. Butterfly pea flowers have many benefits that are rarely known. The butterfly pea flower research method uses maceration extraction. This method is the most commonly used simple method. In addition, the maceration extraction method is also used so that the compounds in the butterfly pea flower are not damaged. The presence of anthocyanin compounds makes the butterfly pea flower have a beautiful color. The content of this anthocyanin phytochemical compound is used as a natural dye in food, this is because the butterfly pea flower has good stability. Other phytochemicals contained in butterfly pea flowers are flavonoids. The content of these flavonoids serves as a source of antioxidants, which will later be developed in a food product. The potential of the butterfly pea flower extract in food products includes being used as a natural dye for ice lolly, synthetic dye for food grade blue diamond Cl 42090, besides that the butterfly pea extract is also used for tea, and also as a natural coloring agent for traditional foods.